Today Das Williams announced support for moratorium on new offshore oil leases -but continues to support a new offshore oil lease for PXP - Susan Jordan:::::: (Susan Jordan)
Newsletter e-mailed to Susan Jordan supporters regarding how Das Williams got into the race largely because of Jordan's position against PXP drilling.